Gangsta rap - Zephaniah, Benjamin (Bloomsbury ; Distributed to the trade by Holtzbrinck Publishers, 2004)
When teenage Ray and his two friends, Prem and Tyronne, form a successful rap band in the London's East End where they live, they soon find themselves embroiled in increasingly violent gang warfare.